To isolate the variable x, we need to cancel out the -7/8 on the left side by adding its opposite value, which is +7/8, to both sides of the equation.
Therefore, the number that should be added to both sides of the equation x − 7/8 = −5 is +7/8.
What number should be added to both sides of the equation x − 7/8 = −5 to find the value of x ?
17 answers
What is the value of x in the equation x + 0.97 = −2 ?
To isolate the variable x, we need to cancel out the +0.97 on the left side by subtracting its value from both sides of the equation.
x + 0.97 - 0.97 = -2 - 0.97
This simplifies to:
x = -2 - 0.97
x = -2.97
Therefore, the value of x in the equation x + 0.97 = -2 is -2.97.
x + 0.97 - 0.97 = -2 - 0.97
This simplifies to:
x = -2 - 0.97
x = -2.97
Therefore, the value of x in the equation x + 0.97 = -2 is -2.97.
What is the solution of the equation x − 94 = −38
To solve for x in the equation x - 94 = -38, you need to isolate the variable x by adding 94 to both sides of the equation:
x - 94 + 94 = -38 + 94
This simplifies to:
x = 56
Therefore, the solution to the equation x - 94 = -38 is x = 56.
x - 94 + 94 = -38 + 94
This simplifies to:
x = 56
Therefore, the solution to the equation x - 94 = -38 is x = 56.
What is the solution of the equation x − 9/4 = −3/8
To solve for x in the equation x - 9/4 = -3/8, you need to isolate the variable x by adding 9/4 to both sides of the equation:
x - 9/4 + 9/4 = -3/8 + 9/4
This simplifies to:
x = -3/8 + 9/4
To add the fractions, you need a common denominator, which is 8:
x = -3/8 + 9/4
= -3/8 + 18/8
= 15/8
Therefore, the solution to the equation x - 9/4 = -3/8 is x = 15/8.
x - 9/4 + 9/4 = -3/8 + 9/4
This simplifies to:
x = -3/8 + 9/4
To add the fractions, you need a common denominator, which is 8:
x = -3/8 + 9/4
= -3/8 + 18/8
= 15/8
Therefore, the solution to the equation x - 9/4 = -3/8 is x = 15/8.
Which of the following should be done to both sides of the equation x + 11 = −17 to solve the value of x? (1 point)
Responses
subtract 11
subtract 11
add 17
add 17
subtract 17
subtract 17
add 11
Responses
subtract 11
subtract 11
add 17
add 17
subtract 17
subtract 17
add 11
To solve for x in the equation x + 11 = -17, you need to isolate the variable x. To do this, you should subtract 11 from both sides of the equation.
Therefore, the correct response is: "subtract 11".
Therefore, the correct response is: "subtract 11".
What is the solution of the equation x + 23 = 9?(1 point)
Responses
32
32
−14
negative 14
−32
negative 32
14
Responses
32
32
−14
negative 14
−32
negative 32
14
To solve for x in the equation x + 23 = 9, you need to isolate the variable x by subtracting 23 from both sides of the equation:
x + 23 - 23 = 9 - 23
This simplifies to:
x = -14
Therefore, the solution to the equation x + 23 = 9 is x = -14.
x + 23 - 23 = 9 - 23
This simplifies to:
x = -14
Therefore, the solution to the equation x + 23 = 9 is x = -14.
Which of the following equations has a solution of −8?(1 point)
Responses
x − 8 = 0
x minus 8 equals 0
x − 4 = −12
x minus 4 equals negative 12
x + 3 = −11
x plus 3 equals negative 11
x − 10 = 2
Responses
x − 8 = 0
x minus 8 equals 0
x − 4 = −12
x minus 4 equals negative 12
x + 3 = −11
x plus 3 equals negative 11
x − 10 = 2
To find the equation that has a solution of -8, we need to substitute -8 for x one by one in each of the equations given and see which one satisfies the equation.
a) x - 8 = 0
Substituting x = -8, we get: -8 - 8 = -16, which is not equal to 0.
b) x - 4 = -12
Substituting x = -8, we get: -8 - 4 = -12, which is not equal to -12.
c) x + 3 = -11
Substituting x = -8, we get: -8 + 3 = -5, which is not equal to -11.
d) x - 10 = 2
Substituting x = -8, we get: -8 - 10 = -18, which is not equal to 2.
None of the equations have a solution of -8.
Therefore, none of the given equations have a solution of -8.
a) x - 8 = 0
Substituting x = -8, we get: -8 - 8 = -16, which is not equal to 0.
b) x - 4 = -12
Substituting x = -8, we get: -8 - 4 = -12, which is not equal to -12.
c) x + 3 = -11
Substituting x = -8, we get: -8 + 3 = -5, which is not equal to -11.
d) x - 10 = 2
Substituting x = -8, we get: -8 - 10 = -18, which is not equal to 2.
None of the equations have a solution of -8.
Therefore, none of the given equations have a solution of -8.
Which of the following should be done to both sides of the equation x − 3.41 = −19 to solve the value of x?(1 point)
Responses
add 19
add 19
add 3.41
add 3.41
subtract 3.41
subtract 3.41
subtract 19
Responses
add 19
add 19
add 3.41
add 3.41
subtract 3.41
subtract 3.41
subtract 19
To solve the equation x - 3.41 = -19, you need to isolate the variable x. To do this, you should add 3.41 to both sides of the equation.
Therefore, the correct response is: "add 3.41".
Therefore, the correct response is: "add 3.41".
Which of the following equations has a solution of −12?(1 point)
Responses
x + 12 = −1
x plus Start Fraction 1 over 2 End Fraction equals negative 1
x − 12 = 1
x minus Start Fraction 1 over 2 End Fraction equals 1
x − 1 = −12
x minus 1 equals negative Start Fraction 1 over 2 End Fraction
x + 1 = 12
Responses
x + 12 = −1
x plus Start Fraction 1 over 2 End Fraction equals negative 1
x − 12 = 1
x minus Start Fraction 1 over 2 End Fraction equals 1
x − 1 = −12
x minus 1 equals negative Start Fraction 1 over 2 End Fraction
x + 1 = 12
To find the equation that has a solution of -12, we need to substitute -12 for x one by one in each of the equations given and see which one satisfies the equation.
a) x + 12 = -1
Substituting x = -12, we get: -12 + 12 = 0, which is not equal to -1.
b) x - 12 = 1
Substituting x = -12, we get: -12 - 12 = -24, which is not equal to 1.
c) x - 1 = -12
Substituting x = -12, we get: -12 - 1 = -13, which is not equal to -12.
d) x + 1 = 12
Substituting x = -12, we get: -12 + 1 = -11, which is not equal to 12.
None of the equations have a solution of -12.
Therefore, none of the given equations have a solution of -12.
a) x + 12 = -1
Substituting x = -12, we get: -12 + 12 = 0, which is not equal to -1.
b) x - 12 = 1
Substituting x = -12, we get: -12 - 12 = -24, which is not equal to 1.
c) x - 1 = -12
Substituting x = -12, we get: -12 - 1 = -13, which is not equal to -12.
d) x + 1 = 12
Substituting x = -12, we get: -12 + 1 = -11, which is not equal to 12.
None of the equations have a solution of -12.
Therefore, none of the given equations have a solution of -12.